2013
DOI: 10.1016/j.ophtha.2012.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Citation of Previous Meta-analyses on the Same Topic

Abstract: Clinical relevance Systematic reviews and meta-analyses serve as a basis for decision-making and clinical practice guidelines and should be carried out using appropriate methodology to avoid incorrect inferences. Topic We describe the characteristics, statistical methods used for meta-analyses, and citation patterns of all 21 glaucoma systematic reviews we identified pertaining to the effectiveness of prostaglandin analog eye drops in treating primary open-angle glaucoma, published between December 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Conventional pair-wise meta-analyses, summarizing these RCTs, can only answer questions where RCTs exist and can only examine pairs of interventions. 9 This does not support real world clinical decision-making because each meta-analysis only takes into account one part of the overall range of choice. It is also worth noting that 43% of pair-wise meta-analyses published up to February 2012 on glaucoma medications used problematic statistical analyses, calling conclusions from these meta-analyses and systematic reviews into question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional pair-wise meta-analyses, summarizing these RCTs, can only answer questions where RCTs exist and can only examine pairs of interventions. 9 This does not support real world clinical decision-making because each meta-analysis only takes into account one part of the overall range of choice. It is also worth noting that 43% of pair-wise meta-analyses published up to February 2012 on glaucoma medications used problematic statistical analyses, calling conclusions from these meta-analyses and systematic reviews into question.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that 43% of pair-wise meta-analyses published up to February 2012 on glaucoma medications used problematic statistical analyses, calling conclusions from these meta-analyses and systematic reviews into question. 9 One common error was that the review authors pooled data by treatment group rather than analyzing the between group effect estimates, breaking the randomized nature of trials. 9 We used three approaches to examine the inconsistency assumption for our network meta-analysis and found that this assumption is likely to hold in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…100,101 In some cases, existing reviews were unreliable because of the lack of adherence to reporting standards and use of systematic review methodology aimed at minimizing selection and reporting biases. Publication of unreliable reviews represents a waste of resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the validity of the results of a network meta-analysis depends on the validity of the assumptions being made, the results depend on the network definitions applied, and the treatment rankings are associated with uncertainty. Although these issues have been discussed extensively in the network meta-analysis literature (5, 6, 45, 46), they may not be familiar to guidelines producers and clinicians.…”
Section: Discussionmentioning
confidence: 99%